POTENSI GAMAL (Gliricidia sepium) SEBAGAI BAHAN BAKU PEMBANGKIT LISTRIK TENAGA BIOMASSA STUDI KASUS : KABUPATEN MANGGARAI TIMUR (NTT) - Dedi Hudaedi; Hariyadi Hariyadi; Syaiful Anwar (Journal of Environmental Engineering and Waste Management, 2018)
The ability of East Manggarai Regency to meet the electricity needs of the region is estimated at only 44.91%. This metter is caused by natural conditions that have a dry climate and critical land, making it difficult to can improve of community economy and generaly region for development of adequate electricity. Therefore, the electrical energi need has been to development challenge, while fossil energi untenable. The construction of a biomass from the Gamal (Gliricidia sepium) plant is a potential alternative to develop. This research aimed to identify the potential lands for Gamal and predict the electricity potency. The method was image analysis from Citra TM 8 using GIS Version 10.1 as an analysis tool. Collecting data was through community interviews with purposive sampling method. The results of this study described the degraded land areas of 187.462,01 hectares which are the potential land for Gamal planting. Prediction of critical lands could produce 98 181.76 m3 of wood products and generate 18.90 MW / year of electricity.